Pulmonary rehabilitation for pneumoconiosis: protocol for a systematic review and meta-analysis. Issue 8 (22nd August 2019) - Zhao, Hulei; Xie, Yang; Wang, Jiajia; Li, Xuanlin; Li, Jiansheng
Abstract : Introduction: Pneumoconiosis is characterised by diffuse fibrosis in lung tissue, and its incidence is on the rise. At present, there are limited therapeutic options for pneumoconiosis. Pulmonary rehabilitation (PR) has been widely used to treat pneumoconiosis，however, there is limited evidence concerning its efficacy. Therefore, we plan to conduct a systematic review to investigate the efficacy and safety of PR for pneumoconiosis. Methods and analysis: The following databases will be searched from their inception to 1 April 2019: PubMed, Embase, The Cochrane Library, Web of Science, Chinese Biomedical Literature Database, China National Knowledge Infrastructure, Chongqing VIP and Wanfang Data. Randomised controlled trials of PR for pneumoconiosis will be included. Primary outcomes will include 6 min walk distance and St. George's Respiratory Questionnaire. Study selection, extraction of data and assessment of study quality each will be independently undertaken. Statistical analysis will be conducted using Review Manager software. Ethics and dissemination: This systematic review will provide up-to-date information on PR for pneumoconiosis. The review does not require ethical approval and will be disseminated electronically through a peer-reviewed publication or conference presentations. PROSPERO registration number: CRD42018095266.